Estimation of goat foetal age during pregnancy using transrectal and transabdominal probes in ultrasound scanning / Mohd. Nizam Abdul Rashid - Mohd. Nizam, Abdul Rashid (2011)
Pregnancy diagnosis plays important role in modern goat management, especially when technologies such as artificial insemination and embryo transfer are employed in goat. Accurate pregnancy diagnosis may provide essential information for effective herd management in farm animals (Doize et al., 1997). This study was carried out with the following objectives: a) to determine accuracy of pregnancy prediction by using ultrasound scanner, b) to determine the criteria for single and twin pregnancies using ultrasound scanner, c) to predict the gestation age based on ultrasound scanning using constructed regression equation, d) to compare the efficacy of two different probes on pregnancy diagnosis and e) to determine the effect of breeds and unknown date of mating on pregnancy diagnosis, using ultrasound scanning. Pregnancy diagnosis was conducted using real-time B-mode ultrasound scanner with transrectal (7.5 MHz) and transabdominal (5.0 MHz) probes. Experiments 1 and 2 were conducted as preliminary studies on detection of pregnancy-related structures and their echogenicity. Experiments 3 and 4 were designed for echogenicity and size measurement of pregnancy-related structures, using both probes as well as to derive equations for gestational age estimation. Flock test was conducted in Experiment 5 to test the accuracy of gestational age estimation equations derived from Experiments 3 and 4. Embryonic vesicles with foetus and foetal heart were detected on week 4 and week 5 of gestation, respectively. Single and twin foetuses were differentiated between weeks 4 to 7 and weeks 5 to 10 of gestation, respectively. Both probes firstly detected placentome on week 7 of gestation and measurable up to the delivery day (week 21 of gestation). Foetal heart measurement was possible starting from week 8 of gestation, owing to the changes in echogenicity of the foetal heart. Transrectal probe visualised foetal heart up to week 10 of gestation, while transabdominal probe until week 21 of gestation. Skeletal structures, such as foetal head, were first viewed on week 6 and week 7 of gestation using transrectal and transabdominal probes, respectively. From Experiment 5, polynomial relationship between foetal heart area and gestational age (single pregnancy: y = 0.033x2 - 0.129x - 0.842; twin pregnancy: y = 0.088x2 – 1.501x + 7.274; where y: heart area (cm2), x: gestational age (week)) gave highest accuracy with 58% accuracy for 1 week delivery difference and maximum accuracy of 94%, of which does delivered within 3 weeks difference from estimated date. Equation for gestational age estimation from placentome diameter derived from current research data (y = -0.016x2 + 0.605x - 1.759; where y: placentome diameter (cm), x: gestational age (week)) only gave 8% and 38% accuracy, respectively. In summary, transrectal probe is reliable to detect pregnancy and estimate gestational age from weeks 4 to 10 of gestation, while transabdominal probe from weeks 5 to 21 of gestation. Foetal heart is proved to be a reliable indicator for determination of foetal number, viability of foetus and gestational age of goats. It is hoped that, in the near future, the outcomes of ultrasound scanning studies on pregnancy diagnosis will complement efficiently with other farm management practices for goat industry.